Assessment of immunotherapy response in intracranial malignancy using semi-automatic segmentation on magnetic resonance images - Tan, Jia; Liu, Chang; Li, Yan; Ma, Yiqi; Xie, Ruoxi; Li, Zheng; Wan, Hengjiang; Lui, Su; Wu, Min (Frontiers in Immunology, 2022)
Objective To explore multi-aspect radiologic assessment of immunotherapy response in intracranial malignancies based on a semi-automatic segmentation technique, and to explore volumetric thresholds with good performance according to RECIST1.1 thresholds. Methods Patients diagnosed with intracranial malignancies and treated with immunotherapy were included retrospectively. In all MR images, target lesions were measured using semi-automatic segmentation technique which could intelligently generate visual diagrams including RECIST1.1, total volume and max. 3D diameter. The changes of parameters were calculated for each patient after immunotherapy. The ROC curve was used to analyze the sensitivity and specificity of the size change of the legion, which was useful to find new volumetric thresholds with good efficiency of response assessment. The changes of total volume were assessed by conventional volumetric thresholds, while RECIST1.1 thresholds were for the max. 3D diameter. Chi-square test was used to compare the concordance and diagnostic correlation between response assessments results of the three criteria. Results A total of 20 cases (Average Age, 58 years; Range, 23 to 84 years), and 58 follow-up MR examinations after immunotherapy were included in the analysis. P value of the chi-square test between RECIST1.1 and total volume is 0 (P < 0.05), same with that in RECIST1.1 and max. 3D diameter. Kappa value of the former two was 0.775, and the Kappa value for the latter two was 0.742. Above results indicates a significant correlation and good concordance for three criteria. In addition, we also found that the volumetric assessment had the best sensitivity and specificity for immunotherapy response in intracranial malignancies with PR threshold of -64.9% and PD threshold of 21%. Conclusions Radiologic assessment of immunotherapy response in intracranial malignancy can be performed by multiple criteria based on semi-automatic segmentation technique on MR images, such as total volume, max. 3D diameter and RECIST1.1. In addition, new volumetric thresholds with good sensitivity and specificity were found by volumetric assessment.